If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -16 = a + -5 Reorder the terms: -16 + 4a = a + -5 Reorder the terms: -16 + 4a = -5 + a Solving -16 + 4a = -5 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -16 + 4a + -1a = -5 + a + -1a Combine like terms: 4a + -1a = 3a -16 + 3a = -5 + a + -1a Combine like terms: a + -1a = 0 -16 + 3a = -5 + 0 -16 + 3a = -5 Add '16' to each side of the equation. -16 + 16 + 3a = -5 + 16 Combine like terms: -16 + 16 = 0 0 + 3a = -5 + 16 3a = -5 + 16 Combine like terms: -5 + 16 = 11 3a = 11 Divide each side by '3'. a = 3.666666667 Simplifying a = 3.666666667
| 16-n/8=-6 | | -2x-9=11+3x | | 21x^2-18x-5=0 | | 7x+3=24+4x | | 8x^3+x^2-55x+42=0 | | x^5-3x^4+10=0 | | 2x^3-6x+3=0 | | -32-3x=5x-37 | | 2=x^2-8+5 | | 1+2x^2-x^4=0 | | 3x(x-5)=4x | | 3(a+2)=-5-2(a-3) | | w/7+9=-3 | | -3(3d-2)=4-d | | 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t | | 4(x+6)-4=6(x+3)-6 | | 6y-5=7y | | 4x-6=x+49 | | 1.25a=1.22 |